Meningioma and Cerebral Spindle Cell Sarcoma as Two Different Metachronous Tumor Entities Secondary to Medulloblastoma Treatment in Childhood: Case Report and Review of the Literature - Jung, Anna; Brodhun, Michael; Lemmer, Andreas; Gerlach, Rüdiger (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2025)
The authors report on a 21-year-old clinically asymptomatic female patient, who was admitted with two supratentorial intradural lesions in her follow-up magnetic resonance imaging 17 years after treatment of a posterior fossa medulloblastoma. Sequential surgical removal was performed. The left parietal tumor with dural involvement was diagnosed as a transitional meningioma WHO (World Health Organization) grade 1. The right temporal lesion, which had also close relationship to the dura, was diagnosed as a spindle cell sarcoma. We therefore report a metachronous tumor development of a benign and a malignant intradural sarcomatous tumor as secondary neoplasms following childhood medulloblastoma treatment.
Keywords: spindle cell sarcoma; meningioma; medulloblastoma